Keanekaragaman kumbang sungut panjang (Coleoptera: Cerambycidae) di Hutan Lindung Wehea, Kalimantan Timur - Sugiarto Sugiarto; Chandradewana Boer; Djumali Mardji; Liris Lis Komara (Perhimpunan Entomologi Indonesia, 2018)
The cerambycid (longhorn) beetles are a diverse, economically important group of insects, associated with a wide variety of plant hosts and amongst the most popular beetle families. The presence of this family in Wehea Protection Forest (WPF) in Muara Wahau Sub-district, East Kutai District of East Kalimantan Province has not been investigated yet, so this paper is the first report of cerambycid beetles diversity in WPF. The objective of this study was to investigate the longhorn beetle species diversity, dominant, and subdominant species, and evenness distribution of individual in WPF area. The beetle was caught using a malaise trap and a trap from jackfruit leaves (Artocarpus heterophyllus) in a sample plot measured 20 m x 100 m (0.2 ha). This study revealed that Simpson’s diversity index was 0.93 (high diversity) and among the 42 species found, a total of 6 species were dominant, 8 species were subdominant, and 28 species were non-dominant. The dominant species were Epepeotes spinosus (Thomson), E. luscus (Fabricius), Acalolepta rusticatrix (Fabricius), Ropica quadricristata (Breuning), Pterolophia melanura Pascoe, and Egesina (Callienispia) minuta (Fisher). Simpson’s evenness index (E) was 0.36 (uneven distributed number of individual between species).